TE Mode Mixing Dynamics in Curved Multimode Optical Waveguides (Communications in Computational Physics, 2020)
Propagation of light through curved graded index optical waveguides supporting an arbitrary high number of modes is investigated. The discussion is restricted to optical wave fields which are well confined within the core region andlosses through radiation are neglected. Using coupled mode theory formalism, twonew forms for the propagation kernel for the transverse electric (TE) wave as it travels along a curved two-dimensional waveguide are presented. One form, involvingthe notion of "bend" modes, is shown to be attractive from a computational point ofview as it allows an efficient numerical evaluation of the optical field for sharply bentwaveguides.